Strategizing Antiviral Medication Usage for Chronic Kidney Disease Patients with SARS-CoV-2: Insights from Inpatient Pharmacy Practices at Hospital Settings - Yuneka Saristiana; Leny Witaning Kusumati; Neni Probosiwi; Tsamrotul Ilmi; Nur Fahma Laili; Fendy Prasetyawan (Journal Health of Indonesian, 2024)
The emergence of the SARS-CoV-2 virus in 2020 led to the onset of the COVID-19 pandemic, posing significant challenges globally. As of December 19, 2021, the worldwide confirmed cases surpassed 273 million, with a devastating death toll exceeding 5.3 million. Indonesia reported its first case on March 2, 2020, and has since faced escalating numbers, necessitating urgent attention.Chronic kidney disease (CKD) has emerged as a commonly occurring comorbidity among COVID-19 patients, drawing attention due to the vulnerability of CKD patients to medical complications. Understanding the use of antiviral drugs in CKD patients with COVID-19 is essential, considering the risks of drug toxicity and interactions. This study aims to investigate the frequency of antiviral drug usage in COVID-19 patients with CKD, providing insights into treatment strategies and guiding medical practitioners. Conducted at Dr. Soedomo Trenggalek Regional Hospital, the research utilizes a cross-sectional, non-experimental design and purposive sampling method. Data collection involves patients' medical records, focusing on demographics, antiviral drug usage, disease severity, treatment duration, mortality rates, and potential side effects. The demographic analysis reveals that the majority of COVID-19 patients with CKD are aged 50 and above, with males comprising 74% of the cohort. Age and gender influence disease severity, with older individuals and males at higher risk. Antiviral drug usage predominantly includes favipiravir (64%) and remdesivir (36%), underscoring their importance in treatment protocols. Decisions regarding antiviral therapy in CKD patients with COVID-19 require careful consideration of benefits, risks, and patient characteristics.